2013
DOI: 10.1556/aagr.61.2013.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of genotype × environment interaction in wheat-barley disomic addition lines

Abstract: In order to locate QTLs controlling the phenotypic stability and drought tolerance of yield and yield components in barley, seven disomic addition lines were sown together with their parents (donor and recipient) in a randomized complete block design with three replications under four rainfed and irrigated conditions. The descriptive diagram of yield and yield components exhibited a genotype (G) × environment (E) interaction and moderate variability over different environments, indicating the possibility of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 35 publications
8
63
0
2
Order By: Relevance
“…The AMMI analysis of variance of grain yield of the fifty five genotypes tested in three environments showed that 71.65% of the total sum of squares was attributable to genotypic effects, 10.51%to environmental effects and 17.83% to genotype × environment interaction effects (Table 2). This is in accordance with the report of Kaya et al (2006);Farshadfar et al (2012) and Mohamed et al (2013). In their study, the effects of E, G and GEI accounted for 81, 7.3 and 11.7% of the total treatments variation respectively.…”
Section: Resultssupporting
confidence: 93%
“…The AMMI analysis of variance of grain yield of the fifty five genotypes tested in three environments showed that 71.65% of the total sum of squares was attributable to genotypic effects, 10.51%to environmental effects and 17.83% to genotype × environment interaction effects (Table 2). This is in accordance with the report of Kaya et al (2006);Farshadfar et al (2012) and Mohamed et al (2013). In their study, the effects of E, G and GEI accounted for 81, 7.3 and 11.7% of the total treatments variation respectively.…”
Section: Resultssupporting
confidence: 93%
“…An interesting application of GGE biplot software is the evaluation of genotype relative to an ideal genotype. The ideal genotype as virtual genotype is one that has both high mean yield across test environments and is absolutely stable in performance (Yan and Rajcan, 2002;Yan and Kang, 2003;Farshadfar et al, 2012). This genotype has large PC1 scores (high mean yield) and small (absolute) PC2 scores (high stability).…”
Section: Evaluation Of Genotypes Relative To Idealmentioning
confidence: 99%
“…Thus, using the ideal genotype as the centre, concentric circles were drawn to help visualize the distance between each genotype and the ideal genotype (Yan and Tinker, 2005). The ranking based on the genotype -focused scaling assumes that stability and mean yield are equally important (Farshadfar et al, 2012;Yan and Hunt, 2001). Fig.…”
Section: Fig 2 Ammi Biplot Graph For Ipca 2 and Grain Yield Genotymentioning
confidence: 99%